CONSERVATION STRATEGIES IN A CHANGING CLIMATE—MOVING BEYOND AN “ANIMAL LIBERATION/ENVIRONMENTAL ETHICS” DIVIDE - PALMER, CLARE (Les ateliers de l'éthique / The Ethics Forum, 2018)
This paper argues that there is no simple rift between animal liberation and environmental ethics in terms of strategies for environmental conservation. The situation is much more complicated, with multiple fault lines that can divide both environmental ethicists from one another and animal ethicists from one another—but that can also create unexpected convergences between these two groups. First, the paper gives an account of the alleged rift between animal liberation and environmental ethics. Then it’s argued that this rift was always exaggerated. For instance, animal ethicists who prioritize aggregate animal welfare have always converged with environmental ethicists in supporting certain cases of hunting and culling, and, in doing so, they have diverged from animal rights theorists, who generally oppose these practices. Pervasive threats such as climate change make it likely that environmental ethicists will also diverge from one another in terms of the conservation strategies they support, depending on what values they prioritize. For instance, conservation strategies that protect species may not necessarily protect other environmental values such as ecosystem flourishing or wildness. The paper concludes that conservation under climate change is likely to bring both new divergences and new convergences, and that these are unlikely to take the form of a rift between animal liberation and environmental ethics.